Carbonodraco lundi gen et sp. nov., the oldest parareptile, from Linton, Ohio, and new insights into the early radiation of reptiles. Issue 11 (27th November 2019) - Mann, Arjan; McDaniel, Emily J.; McColville, Emily R.; Maddin, Hillary C.
Abstract : Redescription of the holotype specimen of Cephalerpeton ventriarmatum Moodie, 1912, from the Middle Pennsylvanian (Moscovian) Francis Creek Shale of Mazon Creek, Illinois, confirms that it is a basal eureptile with close postcranial similarities to other protorothyridids, such as Anthracodromeus and Paleothyris . The skull is long and lightly built, with large orbits and a dorsoventrally short mandible similar to most basal eureptiles. Two specimens referred previously to Cephalerpeton cf. C . ventriarmatum from the approximately coeval Linton, Ohio, locality differ significantly from the holotype in cranial and mandibular proportions and tooth morphology. This material and an additional Linton specimen compare favourably to 'short-faced' parareptiles, such as Colobomycter and Acleistorhinus, and justify recognition of an acleistorhinid parareptile in the Linton assemblage. The new binomen is thus the oldest known parareptile.